Sistem Pakar Cara Mendidik Anak Pelajaran Agama Islam Sesuai Al-Qur'an Menggunakan Metode Forward Chaining - Maulidan, Farid; Dwi Suhendra, Christian; Juita, Ratna (Journal of Applied Informatics and Computing, 2023)
The Al-Qur'an indirectly provides methods for educating children from an early age, as listed in Al-Ahqaf [46]: 30. The implementation of these educational methods requires an expert, specifically an Islamic religious teacher who can suggest appropriate methods to use. Hence, in this context, there is a need to develop an expert system application that can assist teachers in recommending suitable educational methods to parents or guardians based on the child's behavior input. The "expert-mendidik-islam.com" application is created using the forward chaining method, which is employed for reasoning in the database system through rules derived from interviews with experts. The existing child behaviors and rules can be added through the admin page. To evaluate the application, a Likert model questionnaire was administered to parents or guardians of students at SDN 44 Amban and SDN 48 Inggramui, Manokwari Regency. The questionnaire results consistently scored above 80%, indicating that the users strongly agreed with the questionnaire and the application's effectiveness.